2006
DOI: 10.1021/pr0504844
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Assisted Protein Enrichment and Electroelution for Biological Samples Containing Low Protein ConcentrationA Prelude of Gel Electrophoresis

Abstract: Protein enrichment is essential for biological samples that contain low protein concentrations, especially for proteomic studies that require sufficient quantities for subsequent MS analysis. Traditional precipitation methods, however, are limited in the sample volume and protein concentration required to cause efficient precipitations. We showed that gold nanoparticles (Au-NPs) can be easily applied to concentrate proteins from more than 15 mL of human urine, in which the total protein concentration is less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Probe Fabrication-AuNPs, at a concentration of ϳ10 nM, were prepared by sodium citrate reduction following the procedures reported earlier (16). For the fabrication of the AuNP-PEG negative probe, a volume of 10 l of 500 M HS-PEG (molecular weight, 750) was added to 1 ml of synthesized AuNPs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Probe Fabrication-AuNPs, at a concentration of ϳ10 nM, were prepared by sodium citrate reduction following the procedures reported earlier (16). For the fabrication of the AuNP-PEG negative probe, a volume of 10 l of 500 M HS-PEG (molecular weight, 750) was added to 1 ml of synthesized AuNPs.…”
Section: Methodsmentioning
confidence: 99%
“…1C, except when centrifuged, AuNPs remain soluble and well suspended throughout the pulldown process regardless of the buffer exchange. Such advantage is superior to many other nanomaterials and is particularly useful for affinity capturing from a relatively large volume of dilute biological fluids up to several liters (16). Another unique advantage of using AuNPs as probes is the visual monitoring of the modification.…”
Section: Table I Ere Complex Proteins With Significant Changes After mentioning
confidence: 99%
See 1 more Smart Citation
“…This Au@magnetic particle-based strategy was employed to concentrate low amounts of peptide residues from the tryptic digest products of cytochrome c (10 7 M) and the trapping capacity of the Au@magnetic particles for cytochrome c was estimated to be 54 pmol/mg. In another work which also selected AuNPs as sorbents for protein enrichment, Wang et al [42] showed that gold nanoparticles could concentrate proteins from more than 15 mL of human urine, in which the total protein concentration is less than 1.4 ppm. It is noticeable that the AuNP-aggregated proteins could be directly applied to gel electrophoresis for free protein separation as well as for the subsequent in-gel digestion and protein identification by mass spectrometry.…”
Section: Enrichment Of Low-abundance Peptides/proteinsmentioning
confidence: 99%
“…Citrate-capped AuNPs were extensively used for selective enrichment of proteins [20], indoleamines [21], and polycyclic aromatic hydrocarbons [22]. Researchers successfully concentrated aminothiols from urine and serum using Tween 20-modified AuNPs [23,24].…”
Section: Introductionmentioning
confidence: 99%